The Effect Of Electronic Word Of Mouth And Company Image On Customer Loyalty To Indonesian Sharia Banks With Satisfaction As An Intervening Variable - Samapta Rahma Aji; Nurhidayah; Harun Al Rasyid (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the effect of Electronic Word of Mouth (EWOM) and Company Image on Customer Loyalty, with Customer Satisfaction as an intervening variable at Bank Syariah Indonesia (BSI) KCP Batu Diponegoro. The background of this study is the importance of customer loyalty amid digital banking competition. This quantitative study uses an explanatory design with 150 BSI customer respondents, selected through accidental sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0. The results show that EWOM and Corporate Image have a positive and significant effect on Customer Satisfaction and Loyalty. Customer Satisfaction also has a significant effect on Customer Loyalty. The most important finding is that Customer Satisfaction significantly mediates the relationship between EWOM and Corporate Image on Customer Loyalty. It is concluded that EWOM and Corporate Image are drivers of loyalty, but their impact is significantly strengthened when both factors are successfully converted into a satisfying customer experience. Banks are advised to actively manage their digital reputation and improve service quality to ensure satisfaction